57.4k views
3 votes
Evaluate f(x)=x+3for f(-2)

User Jhorton
by
6.0k points

2 Answers

0 votes

Evaluate f(x) = x + 3 for f(-2)

Given: x = -2

Plug in -2 for x in the equation:

f(x) = x + 3

f(-2) = (-2) + 3

f(-2) = 3 - 2

f(-2) = 1

f(-2) = 1

1 is your answer.

~

User Talha Masood
by
5.6k points
1 vote

Answer:

f(-2) = 1.

Explanation:

If we are solving for f(-2), we will simply need to substitute in '-2' for 'x'. This gives us:

f(-2) = -2 + 3

f(-2) = 1.

User Kirill Salykin
by
5.7k points